ENaC Dysregulation Through Activation of MEK1/2 Contributes to Impaired Na+ Absorption in Lymphocytic Colitis. Issue 3 (March 2016) - Barmeyer, Christian; Erko, Irene; Fromm, Anja; Bojarski, Christian; Loddenkemper, Christoph; Dames, Petra; Kerick, Martin; Siegmund, Britta; Fromm, Michael; Schweiger, Michal R.; Schulzke, Jörg-Dieter
Abstract : Background: Lymphocytic colitis (LC) causes watery diarrhea. We aimed to identify mechanisms of altered Na + absorption and regulatory inputs in patients with LC by examining the epithelial Na + channel (ENaC) function as the predominant Na + transport system in human distal colon. Methods: Epithelial Na + channel function and regulation was analyzed in biopsies from sigmoid colon of patients with LC and in rat distal colon in Ussing chambers. ENaC-subunit expression was measured by real-time PCR and RNA sequencing. Correction factors for subepithelial resistance contributions were determined by impedance spectroscopy. Upstream regulators in LC were determined by RNA sequencing. Results: Epithelial Na + channel-mediated electrogenic Na + transport was inhibited despite aldosterone stimulation in human sigmoid colon of patients with LC. The increase in γ-ENaC mRNA expression in response to aldosterone was MEK1/2-dependently reduced in LC, since it could be restored toward normal by MEK1/2 inhibition through U0126. Parallel experiments for identification of signaling in rat distal colon established MEK1/2 to be activated by a cytokine cocktail of TNFα, IFNγ, and IL-15, which were identified as the most important regulators in the upstream regulator analysis in LC. Conclusions: In the sigmoid colon of patients with LC, the key effector cytokines TNFα, IFNγ, and IL-15 inhibited γ-ENaC upregulation in response to aldosterone through a MEK1/2-mediated pathway. This prevents ENaC to reach its maximum transport capacity and results in Na + malabsorption which contributes to diarrhea. Abstract : Article first published online 29 December 2015.Supplemental Digital Content is Available in the Text.